2014
DOI: 10.1007/s13205-014-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth promotory potential of the cold adapted diazotroph Pseudomonas migulae S10724 against native green gram (Vigna radiata (L.) Wilczek)

Abstract: It is being confirmed previously the atmospheric nitrogen fixing ability of the cold adapted Pseudomonas migulae S10724 strain at the fluctuating temperatures. Therefore, net house bioinoculation experiment was performed to determine the effectiveness of inoculation of strain S10724 on the growth enhancement of native green gram (Vigna radiata L. Wilczek). The strain significantly (p < 0.05) stimulated the growth of roots (45.3 %) and shoots (45.6 %) of green gram plants. Furthermore, other growth related para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…Katiyar and Goel (2003) assessed the inoculation effect of phosphate-solubilizing cold-tolerant mutant of P. fluorescens on mungbean in sterilized and unsterilized soil and observed that inoculated plants resulted in better plant growth in both soils. Moreover, it is also reported that inoculation of the diazotrophic bacterial strains significantly increased the biomass of plants and also had a significant impact on the total N in plant tissues as compared to uninoculated control (Suyal et al, 2014a, Yim et al, 2009. These reports further corroborates with our findings with respect to efficacy of a native diazotrophic strain in improving crop growth parameters and hence increasing crop yield.…”
Section: Evaluation For Plant Growth Promotion Under Nethouse Conditionssupporting
confidence: 91%
See 1 more Smart Citation
“…Katiyar and Goel (2003) assessed the inoculation effect of phosphate-solubilizing cold-tolerant mutant of P. fluorescens on mungbean in sterilized and unsterilized soil and observed that inoculated plants resulted in better plant growth in both soils. Moreover, it is also reported that inoculation of the diazotrophic bacterial strains significantly increased the biomass of plants and also had a significant impact on the total N in plant tissues as compared to uninoculated control (Suyal et al, 2014a, Yim et al, 2009. These reports further corroborates with our findings with respect to efficacy of a native diazotrophic strain in improving crop growth parameters and hence increasing crop yield.…”
Section: Evaluation For Plant Growth Promotion Under Nethouse Conditionssupporting
confidence: 91%
“…Significance of rhizosphere microbiome under several biotic and abiotic stresses has been reviewed by Mendes et al (2013). Previously presence of psychrotolerant diazotrophs of Western Indian Himalayas was reported by Suyal et al (2014a). We, therefore, conducted the present study which focuses on the isolation, identification and application of native psychrotolerant diazotrophic strains under natural fluctuating temperatures which could be explored against the individual or mixed cropping of native E. coracana and C. cajan in upper Himalayan agricultural lands.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sanchez et al (2014) characterized twenty different plant growth promoting bacteria from the rhizosphere of Phaseolus vulgaris. Previous studies confirmed that Himalayan soils have bacterial community with a tremendous potential of biodegradation (Soni et al 2008) and plant growth promotion (Kumar et al 2014;Suyal et al 2014a). Previous studies confirmed that Himalayan soils have bacterial community with a tremendous potential of biodegradation (Soni et al 2008) and plant growth promotion (Kumar et al 2014;Suyal et al 2014a).…”
Section: Introductionmentioning
confidence: 86%
“…JJS2 of Western Indian Himalayas showed good growth on N2-free media at room temperature; their nif H fragment amplification confirms their diazotrophic nature [27]. An inoculation of the diazotrophs significantly improves the crop productivity and biomass in contrast to uninoculated control crop [28].…”
Section: Polysaccharide Production and Growth On N-freementioning
confidence: 99%